India's groundwater storage trends influenced by tube well intensification - Chinnasamy, Pennan; Agoramoorthy, G. (Wiley, 2016)
Agriculture is a major occupation for people who inhabit the state of West Bengal in India. In order to boost irrigation, 570 tube wells per year were installed during 2002-2008, and 12,000 wells per year were installed during 2009-2013, contributing to higher groundwater (GW) withdrawal. However, the impact of tube wells on GW storage levels has not been well-studied, both spatially and temporally. Hence, this study used remote sensing data from NASA's Gravity Recovery and Climate Experiment and the Global Land Data Assimilation Systems to assess change in GW storage. Results showed that GW is being depleted at 8, 5.3, and 14.7 cm (Billion Cubic Meters)/year during the study period. After tube well intensification, the state-wide average net GW recharge was 15.33 BCM/year, while the net GW discharge was at 19 BCM/year. The spatiotemporal GW storage data presented in this paper will benefit managers and policymakers in identifying suitable mitigation plans for future management of GW resources.